Organic Farming in India: Transforming Agriculture for Tomorrow - Kaur, Ramanjit; Sepat, Seema; Ali, Sk Asraful (Chronicle of Bioresource Management, 2025)
Organic farming in India has gained momentum as a sustainable alternative to conventional agriculture, driven by concerns over environmental degradation and resource depletion. Despite its potential to enhance soil health and biodiversity, organic farming faces challenges such as limited awareness, labour shortages, certification hurdles, and underdeveloped supply chains. Research indicates an initial decline in yields during the transition period, but comparable or improved productivity is achievable with proper management. Government initiatives like the National Programme for Organic Production (NPOP), Paramparagat Krishi Vikas Yojana (PKVY), and Mission Organic Value Chain Development for North Eastern Region (MOVCDNER) support organic agriculture through certification and market linkages. However, only a small fraction of India’s agricultural land is organic, making its overall impact on food security modest. Addressing policy gaps, improving input quality, and strengthening market access are crucial for realizing the full benefits of organic farming in India.